2017
DOI: 10.1161/jaha.117.007074
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Metabolic Consequences of Testosterone Supplements in Young and Old Male Spontaneously Hypertensive Rats: Implications for Testosterone Supplements in Men

Abstract: BackgroundThe safety of testosterone supplements in men remains unclear. In the present study, we tested the hypothesis that in young and old male spontaneously hypertensive rats (SHR), long‐term testosterone supplements increase blood pressure and that the mechanism is mediated in part by activation of the renin‐angiotensin system.Methods and ResultsIn untreated males, serum testosterone exhibited a sustained decrease after 5 months of age, reaching a nadir by 18 to 22 months of age. The reductions in serum t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…These findings show that testosterone is important in the hypertensive effect induced by Ang II as withdrawal (castration) prevented Ang II effects and replacement (testosterone) reversed the castration effects on Ang II-induced changes in blood pressure. This suggests that the development of Ang II-induced hypertension is androgen dependent, which appears to be similar to that observed in other in utero programming of increases in blood pressure [20,[43][44][45].…”
Section: Discussionsupporting
confidence: 79%
“…These findings show that testosterone is important in the hypertensive effect induced by Ang II as withdrawal (castration) prevented Ang II effects and replacement (testosterone) reversed the castration effects on Ang II-induced changes in blood pressure. This suggests that the development of Ang II-induced hypertension is androgen dependent, which appears to be similar to that observed in other in utero programming of increases in blood pressure [20,[43][44][45].…”
Section: Discussionsupporting
confidence: 79%
“…3 The average change in ambulatory BP in those men on antihypertensive therapy was prominent in men with underlying hypertension than those without hypertension. Furthermore, Dalmasso C et al 11 have reported that there are differential effects of testosterone on BP in the spontaneously hypertensive rat (SHR) depending on the age of the SHR -an effect that may be mediated in part by the reninangiotensin system.…”
Section: Discussionmentioning
confidence: 99%
“…Hormones such as testosterone are often used as adjuvants, although various adverse reactions have been reported [ 40 , 41 ]. Therefore, developing effective medicines is a core issue in treating age-related reproductive decline.…”
Section: Discussionmentioning
confidence: 99%